Absorption band shape of combined two-dimensio magnetoexciton-cyclotron resonance - Moscalenco, Sveatoslav; Podlesnîi, Ivan; Rusu, Spiridon; Cerbu, Florin; Kiseliova, Elena; Colun, Sergiu; Railean, Oleg; Liberman, Michael (Moldavian Journal of the Physical Sciences, 2008)
The absorption band shape of the combined optical quantum transition with the creation of a two-dimensional magnetoexciton and with the simultaneous excitation of one back- ground electron between its Landau levels is discussed. The combined magnetoexciton- cyclotron resonance (MECR) quantum transitions are described within the frame of the model of two-dimensional electron-hole system in a strong perpendicular magnetic field, taking into account supplementary small concentration of background electrons resident on the lowest Landau level (LLL). The concrete case of magnetoexciton composed by electron and hole on their LLL and the accompanying cyclotron resonance with excitation of the background electron from the LLL to the first excited Landau level is considered. The position of the combined absorption band is shifted in comparison with the frequency of the magnetoexciton band by the frequency of the electron cyclotron resonance. The maximal band width equals the ionization potential l I of the magnetoexciton, because participation of the third particle side by side with the electron-hole pair permits to uncover its entire internal energy spectrum